Biodiversity studies of ruminant Mediterranean species through DNA molecular markers - Avellanet R.; Martín-Burriel I.; Sanz A.; Rodellar C.; Osta R.; Pons A.; Puigserver G.; Segui R.; Alabart J.L.; Folch J.; Crespo M.J.; Argüello S.; et al. (Mediterranean livestock production: uncertainties and opportunities, 2008)
During the last century the ruminant census has suffered an important decrease and breeds in danger of extinction have increased dramatically. The efforts to preserve these breeds have been essential to maintain their biological and ecological potential. The aim of the present work was to carry out biodiversity studies in some Mediterranean cattle, sheep, and goat breeds, through DNA molecular markers such as microsatellites. In this sense, a DNA data bank has been created for each specie. Moreover, several breeds have been genetically characterised and their differentiation and evolutive relationship have been analysed.
2. Seminar of the Scientific-Professional Network on Mediterranean Livestock Farming (RME), 2006/05/18-20, Zaragoza, (Spain)